Pro Spring 3 - Ho, Clarence; Harrop Rob ([Berkeley, Calif.] : Apress ; New York : Distributed to the book trade worldwide by Springer Science+Business Media, 2012)
A guide to the Spring Framework provides instructions for designing and building applications.
Includes index.
A comprehensive reference and practical guide to the spring framework. This is the most comprehensive spring reference and practical guide available for harnessing the power of this leading enterprise java application development framework.
rua 22/10/13
Loans
Keywords: Java (Computer program language); Web site development; Pro spring